Electron swarm and streamer transport across the gas–liquid interface: a comparative fluid model study. (15th October 2018) - Garland, N A; Simonović, I; Boyle, G J; Cocks, D G; Dujko, S; White, R D
Abstract: In this work we present a comparative study of fluid modeling methods in order to determine a recommended procedure to describe electron transport and streamer propagation across gas–liquid interfacial regions. A test case of a cryogenic argon gas–liquid interface is simulated in this work to demonstrate applicability of the recommended procedures. The recommended non-local four moment model takes into consideration the density variation across the interface, and its associated impact on the transport properties/collisional transfer rates, as well as the spatial variation of the dielectric permittivity and the conduction band through the liquid binding energy, V 0 . The study examines the impacts of various assumptions involved in the modeling of electron transport across the plasma-liquid interface, by comparing a local field (drift-diffusion) approximation with the non-local (four moment) model, as well as a step function change in the density to actual spatially dependent density variations across the interface. We provide recommendations on necessary physical considerations needed to adequately model transport phenomena across gas–liquid interfaces.